2002
DOI: 10.1136/gut.50.5.693
|View full text |Cite
|
Sign up to set email alerts
|

Infection rate and spontaneous seroreversion of anti-hepatitis C virus during the natural course of hepatitis C virus infection in the general population

Abstract: Background: Hepatitis C virus (HCV) infection is common worldwide but there are different prevalence rates in different countries. Data on the incidence of HCV in the general population are scarce. Spontaneous viral clearance occurs in 10-25% of infected individuals after acute infection yet controversy exists regarding the frequency of spontaneous clearance during the natural course of HCV infection in the general population. Aims: Anti-HCV prevalence, HCV infection rate, and the kinetics of anti-HCV were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 25 publications
8
69
7
Order By: Relevance
“…In addition, several studies showed no significant relationship between HCV genotypes, replication properties, HCV clearance, and disease outcome (6,31,38,50). A higher rate of chronicity among patients infected with genotype 2c than with genotype 1b was recently reported (22). The high recovery rate and low viral load in HCV chronic infection observed in Ghanaian blood donors (Fig.…”
mentioning
confidence: 83%
“…In addition, several studies showed no significant relationship between HCV genotypes, replication properties, HCV clearance, and disease outcome (6,31,38,50). A higher rate of chronicity among patients infected with genotype 2c than with genotype 1b was recently reported (22). The high recovery rate and low viral load in HCV chronic infection observed in Ghanaian blood donors (Fig.…”
mentioning
confidence: 83%
“…The proportion of confirmed active infections among positive screening test results varies widely across studies and test types. The proportion of RNA-positive, active HCV infection cases ranged from 0% to 89.7% among positive antibody-based assays [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][51][52][53][54] and from 0% to 100% among antigen-based assays. 39,44,49,50 Only three studies conducted confirmatory polymerase chain reaction on samples that tested negative for HCV antibody or antigen.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…The titer of anti-HCV antibodies decrease rapidly in recovered chronically HCV infected patients given interferon-based therapy (Maylin et al, 2009, Toyoda et al, 2005 and can sometimes completely disappear about two decades after HCV recovery (Takaki et al, 2000). Loss of anti-HCV antibodies can be observed in 6 to 20% of immunocompetent patients (Kondili et al, 2002, Lefrere et al, 2004 ). This IgG anti-HCV core test identifies occult HCV infections in seronegative, non-viremic patients and may be useful for tracking infections in patients who test negative for anti-HCV antibodies.…”
Section: Humoral Immune Responsementioning
confidence: 99%